TRACP 5b and CTX as osteological markers of delayed fracture healing - Moghaddam-Alvandi, Arash; Müller, U.; Roth, H. J.; Wentzensen, Andreas; Grützner, Paul Alfred; Zimmermann, Gerald (Injury, 2011)
Radiological studies are the standard method to monitor fracture healing but they do not allow a timely assessment of bone healing. Biochemical markers react rapidly to changes in bone metabolism during fracture healing and could be an additional tool to monitor this process. The goal of this study was to observe changes in serum biomarkers and evaluate the possible differences in the serum levels of tartrate-resistant acid phosphatase 5b (TRACP 5b), total N-terminal propeptide of type I collagen (PINP), bone-specific alkaline phosphatase (BAP), and C-terminal cross-linking telopeptide of type I collagen (CTX) in patients with normal and delayed fracture healing. Several serum samples were collected for one year after the surgical treatment of long bone fractures in 248 patients. From this large pool, 15 patients with atrophic nonunion were matched to 15 patients with normal bone healing. Post-operative changes in osteological markers were monitored during the 1st, 2nd, 4th, 8th, 12th and 52nd weeks. The patients were followed both clinically and radiologically for the entire one-year duration of the study. In the first week, the absolute values of CTX decreased significantly (p=0.0164) in cases of delayed fracture healing. The relative values of TRACP 5b were significantly decreased at weeks 4 (p=0.0066) and 8 (p=0.0043). BAP and PINP levels decreased in the first week followed by an increase, but there were no significant differences in the absolute or relative values during the healing process in both patient groups. For the first time, we have demonstrated changes in serum concentrations of TRACP 5b, PINP, BAP, and CTX during normal and delayed fracture healing. Characteristic changes in systemic TRACP 5b and CTX levels could reflect the initial process of successful fracture healing and may be used in clinical practice to monitor the healing process. Furthermore, it could be very important for determining the beneficial effects of additional treatments such as ultrasound or BMPs in clinical trials.
Available online 17 December 2010
Gesehen am 08.09.2022